The Influence of Attitudes of The Millennial Generation and Brand Awareness on Interest In Buying FastFood at Gozila Corndog On Students Of The Faculty of Economics, Sumatera Barat University - Hendri, Novi; Afriyanti, Ria; Safardi, Safardi; Meidona, Syofria; Amran, Elsa Fitri (Denisya Smart Consulting, 2024)
This research aims to determine the influence of Millennial Generation Attitudes and Brand Awareness on Interest in Buying Fast Food at Gozila Corndog among Students at the Faculty of Economics, Sumatera Barat University. The sample in this research was 87 students from the Faculty of Economics, Sumatera Barat University who were active in 2022-2023. The data collection technique in this research uses a questionnaire with a quantitative approach. The data analysis technique used is multiple linear regression analysis and coefficient of determination. Data processing in this study used IBM SPSS Statistics 25. The results showed that partially the attitude of the millennial generation had a significant effect on buying interest, partially brand awareness has a significant effect on buying interest, and simultaneously (together) the attitude of the millennial generation and brand awareness have a significant effect on buying interest.